2020
DOI: 10.1111/jgs.16748
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Atrial Fibrillation Subtypes in Italy and Projections to 2060 for Italy and Europe

Abstract: BACKGROUND/OBJECTIVES: Atrial fibrillation (AF) subtypes may carry different cardiovascular risk profiles, but information on their frequency from population-based studies is lacking. We estimated prevalence of AF subtypes in a representative sample of the Italian older population, projecting figures for Italy and the European Union. DESIGN: Cross-sectional study. SETTING: Three primary care practices in northern, central, and southern Italy. PARTICIPANTS: All individuals aged 65 years or older, for a total sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Polypharmacy is common in the elderly, often accompanied by AF. 1 2 The meta-analysis by Harskamp et al 16 enrolling two post-hoc analyses of RCTs showed that the frequencies of bleeding events and mortality, but not SSE, were positively associated with the number of concomitant drugs. Our study yielded similar findings after including more high-quality retrospective studies and post-hoc analyses of RCTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polypharmacy is common in the elderly, often accompanied by AF. 1 2 The meta-analysis by Harskamp et al 16 enrolling two post-hoc analyses of RCTs showed that the frequencies of bleeding events and mortality, but not SSE, were positively associated with the number of concomitant drugs. Our study yielded similar findings after including more high-quality retrospective studies and post-hoc analyses of RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is a cardiac arrhythmia that is more common in the elderly, particularly those aged between 65 and 85 years, who make up nearly 70% of AF patients. 1 2 Elderly AF patients often have a heavy comorbidity burden and simultaneously use multiple drugs, a condition known as polypharmacy. However, there is no international consensus on the threshold and measurement methods of drug use.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings come from a population-based, multicentre study with a nationwide representative sample, which makes results transferable to the Italian older population. Data on frequency of AF subtypes were achieved through a combined screening procedure, which reduced the chance of missing AF cases, and on the direct clinical and ECG evaluation of all positive participants [ 29 ]. All the remaining clinical information was collected from the computerized practice records, and directly from the GPs and the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the prevalence is 10% in people >65 years old and >15% among the >80-year-olds 1 . In the coming decades, the prevalence of AF in Europe is calculated to reach ~ 25 million patients 2 3 , likely further elevated by improved detection tools (i. e. smart watches). Atrial fibrillation is one of the leading causes of hospitalization 4 5 6 .…”
Section: Introductionmentioning
confidence: 99%